Properties of GABA(A) Receptors Underlying Inhibitory Synaptic Currents in Neocortical Pyramidal Neurons - Galarreta, Mario (J Neurosci, 1997)
Rapid applications of GABA (from 10 μm to 10 mm) to outside-out patches were used to study the role that the kinetic properties of GABA(A) receptors play in determining the time course of IPSCs in neocortical pyramidal neurons. Currents induced by rapid applications of brief (1 msec) pulses of GABA (1 mm) showed a biexponential decay phase that seems to involve the entry of GABA(A) receptors into desensitized states. This conclusion is based on the similar fast decay kinetics of the response to brief and prolonged pulses of GABA and on the correlation between the degree of paired-pulse depression and the decay rate of the currents induced by brief pulses. Under nonequilibrium conditions we found that the concentration–response curve of pyramidal GABA(A) receptors has an EC(50) of 185 μm (GABA pulse of 1 msec). The decay time course of the patch currents in response to brief applications of GABA was insensitive to agonist concentrations at the range from 50 μm to 10 mm. Faster decay rates were observed only in response to pulses of 10 μm GABA. These data are compatible with the suggestion that briefer openings derive from a monoliganded state and that these are negligible when receptor activation is >2%. Assuming that GABA transients at neocortical synapses are fast, a several millimolar GABA concentration would be needed to saturate the postsynaptic GABA(A)receptors.